موقف النحاة من القراءات: دراسة تأصيليَّة (The view of grammarians on Quranic recitations : A study of origin) - (Saleh Mahjub Mohamed al-Tingari), صالح محجوب محمَّد (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث: رَمَى هذا البحث من خلال المنهج الوصفي الاستقرائي إلى إظهار المرتكزات الأساسية التي ارتكز عليها النحاة في تقعيد النحو العربي، فعلى الرغم من أنَّ النحو نشأ أساساً لخدمة القرآن الكريم إلا أن النحاة اعتمدوا في تقعيدهم للنحو على أشعار العرب وكلامهم، ثم القرآن الكريم في المرتبة الثالثة – في الغالب الأعم – وليتهم توقفوا عند هذا الحدِّ، بل نجد طائفة كبيرة منهم امتدتْ ألسنتها وأقلامها إلى بعض القراءات المتواترة، ووصفتها بالضعف تارة، وباللحن تارة أخرى، وما ذلك إلا لارتطامها بقواعدهم الموضوعة! ويحاول البحث دراسة موقف النحاة عموماً من بصريين وكوفيين من القراءات القرآنية؟ والتأكيد علي أن الاحتجاج بالقراءات عرفته المدرسة البصرية والكوفية إلا أن الأخيرة توسعت فيه. الكلمات المفتاحية: القراءات- نحاة البصرة- نحاة الكوفة- القراء- النحاة. Abstract: This study through the descriptive and deductive methods, aims at pointing out the basis on which the grammarian build their foundation for the Arabic grammar. Although that grammar was established to serve the holy Koran, but the foundation of grammar generally was derived from the Arab poems and their expressions, and the Quranic verses only come at the third position in terms of priority. If this is not appalling, some of the grammarians even criticized the Quranic verses even the most agreed upon in terms of the number of their narrators, as to be ungrammatical or sometimes, erroneous due to their incompliance with the rules that they themselves create. This paper attempts to study both schools of grammar : the Kufan and the Basran to uncover their position with regard to the Quranic verses. It is also an attempt to verify that these grammar schools did make the Quranic verses as their proofs in language argument although that the latter was found to be applying in a wider scope then the former. Keywords: Recitations – Grammarians of Basrah – Grammarians of Kufah – Recitors – Grammarians. Abstrak: Kajian ini tertumpu kepada prinsip-prinsip asas yang dibahaskan oleh ahli- ahli Nahu dalam meletakkan kaedah bahasa Arab. Pada asasnya kaedah nahu dicipta untuk memahami ayat suci A-Quran, akan tetapi terdapat banyak kaedah-kaedah nahu diasaskan berdasarkan syair-syair Arab, kata-kata mereka dan secara umumnya Al-Quran di kedudukan yang ketiga. Malah kita mendapati bahawa sebahagian besar daripada mereka menggunakan qiraat mutawatirah sebagai hujah dalam percakapan mahupun penulisan mereka tetapi menyifatkan qiraat tersebut kadang-kadang sebagai lemah dan adakalanya sebagai salah. Hal yang demikian ini berlaku tidak lain tidak bukan kerana pertembungan qiraat-qiraat tersebut dengan kaedah nahu yang dicipta. Penyelidik cuba mengkaji pendirian ahli-ahli nahu dari aliran Basrah dan Kufah terhadap Qiraat dan membuktikan bahawa mereka mengambil kira Qiraat sebagai hujah. Kata kunci: Qiraat- Ahli Nahu Basrah – Ahli Nahu Kufah – Qari – Nahu.